Bioadhesive Mini-Tablets for Vaginal Drug Delivery - Marianne Hiorth; Susanne Nilsen; Ingunn Tho (MDPI AG, 2014)
Different non-ionic cellulose ethers (methyl cellulose, MC; hydroxyethyl cellulose, HEC; hydroxypropyl cellulose, HPC; hydroxypropylmethyl cellulose, HPMC) and microcrystalline cellulose (MCC) were investigated as matrix formers for preparation of mini-tablets targeting vaginal drug delivery. Hexyl aminolevulinat hydrochloridum (HAL) was used as a model drug. The mini-tablets were characterized with respect to their mechanical strength, bioadhesion towards cow vaginal tissue in two independent tests (rotating cylinder test, detachment test using texture analyzer), and dissolution rate in two media mimicking the pH levels of fertile, healthy and post-menopausal women (vaginal fluid simulant pH 4.5, phosphate buffer pH 6.8). Mini-tablets with a matrix of either HPMC or HPC were found to possess adequate mechanical strength, superior bioadhesive behavior towards vaginal tissue, and pH independent controlled release of the model drug, suggesting that both systems would be suited for the treatment of women regardless of age, i.e., respective of their vaginal pH levels. Bioadhesive mini-tablets offer a potential for improved residence time in the vaginal cavity targeting contact with mucosal tissue and prolonged release of the drug.